NGELIK SILIHAN DALAM KARAWITAN GAYA SURAKARTA - Uni Ambarwati; Suyoto Suyoto (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2019)
This study examines ngelik silihan in Surakarta style music. The problems revealed in this study are (1) How can ngelik in Surakarta style music, (2) Why does the Eling-eling ladrang dish generally use ngelik?, (3) Any factors that support a loan of ngelik silihan. This research is a qualitative research, data obtained from literature studies, observations, and interviews. The theory used as the basis for analyzing in accordance with the formulation of the problem is the creativity theory by Wallas about the process of creativity, and the theory of musical interaction by Benjamin Briner about musical interactions that occur in gending, and the theory of melodic contour by Judith Bekker about the melody flow obtained in theory worked on by Rahayu Supanggah, in the theory of the melodic contour it can emphasize the problem of the melody flow in the interconnected selection. The results of this study found that the use of ngelik silihan there are three factors, namely: 1. Shifting the function of the presentation, 2. Creativity of the artists. The use of ngelik silihan with consideration of the same melodic and song gong grooves, so that it is aligned with the borrowed portion of the loan, 3. Pathet factors for the lending and borrowed selection. In addition there is a historical statement that the Pangkur ladrang borrowed the Eling-eling ladrang. Information on the artist community that the Eling-eling ladrang borrowed the Pangkur ladrang, the reasons are: 1. Recognition of the perpetual artists acquired, 2. Manuscripts in the Mloyowidodo notation book, 3. Commercial cassette tapes which first popularized the Eling-ladrang ladrang from at Pangkur ladrang.Keywords: Ngelik, Silihan, Song, Sèlèh, Gending.